Adenovirus E1A requires synthesis of a cellular protein to establish a stable transcription complex in injected Xenopus laevis oocytes. - Richter, J D (1987)
The Escherichia coli-expressed adenovirus E1A 13S mRNA product injected into Xenopus oocytes was active, as assessed by its ability to stimulate the transcription of an injected gene which is normally responsive to E1A in mammalian cells. In the presence of the protein synthesis inhibitors pactamycin or cycloheximide, E1A was correctly posttranslationally modified (phosphorylated) and transported to the nucleus; but it failed to stimulate the transcription of an injected gene containing the human heat shock protein 70 promoter. The basal (unstimulated) level of transcription of the gene was unaffected by these inhibitors. If oocytes were cultured in the presence of cycloheximide after E1A stimulated transcription, however, the high level of transcription was maintained for several hours without new protein synthesis. Results of competition studies with the same promoter (the heat shock protein 70 promoter) linked to two marked genes demonstrated that once the induction of transcription by E1A took place, the stimulated levels of transcription were maintained, even when they were challenged with excess competitor DNA. Results of these studies suggest that E1A requires the synthesis of a cellular protein to form a stable transcription complex.